Augmented reality in interventional radiology education: a systematic review of randomized controlled trials - Gelmini; Yara Particelli; Duarte, Márcio Luís; Silva, Mayara Oliveira da; Guimarães Junior, Josias Bueno; Santos, Lucas Ribeiro dos (São Paulo Medical Journal, 2022)
BACKGROUND: Augmented reality (AR) involves digitally overlapping virtual objects onto physical objects in real space so that individuals can interact with both at the same time. AR in medical education seeks to reduce surgical complications through high-quality education. There is uncertainty in the use of AR as a learning tool for interventional radiology procedures. OBJECTIVE: To compare AR with other learning methods in interventional radiology. DESIGN AND SETTING: Systematic review of comparative studies on teaching techniques. METHODS: We searched the Cochrane Library, MEDLINE, Embase, Tripdatabase, ERIC, CINAHL, SciELO and LILACS electronic databases for studies comparing AR simulation with other teaching methods in interventional radiology. This systematic review was performed in accordance with PRISMA and the BEME Collaboration. Eligible studies were evaluated using the quality indicators provided in the BEME Collaboration Guide no. 11, and the Kirkpatrick model. RESULTS: Four randomized clinical trials were included in this review. The level of educational evidence found among all the papers was 2B, according to the Kirkpatrick model. The Cochrane Collaboration tool was applied to assess the risk of bias for individual studies and across studies. Three studies showed an improvement in teaching of the proposed procedure through AR; one study showed that the participants took longer to perform the procedure through AR. CONCLUSION: AR, as a complementary teaching tool, can provide learners with additional skills, but there is still a lack of studies with a higher evidence level according to the Kirkpatrick model. SYSTEMATIC REVIEW REGISTRATION NUMBER: DOI 10.17605/OSF.IO/ACZBM in the Open Science Framework database.